Stems' diameter variations to detect sympodial orchids' water stress / Naimah Mat Isa … [et al.] - Mat Isa, Naimah; Mohd Shah Baki, Shah Rizam; Md. Tahir, Nooritawati; Zainol Abidin, Husna; Nordin, Mohd. Khairi (Research Management Institute (RMI), 2012)
The measurements of stems' has played an important indicator for plant's water status. Many researches have been carried out in terrestrial plants to investigate the stems' variations of responses that had inspired to develop a precise irrigation system. Hence, the work presented in this thesis investigates the stems' variations in epiphyte plants that are sympodial orchids. A strain gauge was used as a sensor to measure the orchid's stem variation for 48 days at two stages of measurements. The Dendrobium orchid that grew from tissue culture was chosen as a sampling plant due to its popularity as a cut flower in the world's demand. The experiment was done within 30 days involving 10 samples of orchid plants growing indoor and outdoor. The measurements were recorded every 15 minutes continuously along the experiment executed. The 2 mm aluminium strain gauge and it's signal conditions that integrated with PIC produced a correlation at 0.96 between its output and the changes in displacement. The results showed that the stems' diameter variations in Dendrobium orchids could be manipulated for further analysis and it had played a significant role for triggering further researches in the developments of a precise watering system in the orchid farms.